PTU-042 The Incremental Benefit of Video Capsule Endoscopy after Magnetic Resonance Enterography (MRE) In Patients with Suspected Small Bowel Crohn's Disease. (17th August 2016) - Archer, T; Samuel, S; Simmonds, L; Sikafi, R; Plichta, P
Abstract : Introduction: Video Capsule Endoscopy (VCE) has the unique ability to visualise the small intestinal mucosa, which traditionally is difficult to reach with a standard endoscope. The indications for this test are primarily to investigate the small bowel (SB) in patients with Crohn's Disease (CD) and to evaluate the SB for causes of Iron Deficiency Anaemia (IDA). Despite the high diagnostic yield with VCE, one of its main drawbacks is its low specificity in patients with inflammatory bowel disease (IBD). In a prospective blinded 4 way comparison study, capsule endoscopy had a sensitivity of 83% and a specificity of 53%. 1 We intended to evaluate the additional benefit of VCE in our patient cohort with particular emphasis on those patients who had MRE prior to their VCE as part of their work up for IBD. Methods: Patients who had VCE in Nottingham University Hospitals NHS Trust between January 1 st 2014 and January 1 st 2016 were included. Patient data including demographics, previous investigations and the treating physician's interpretation of results and resultant change in management, from these investigations, were abstracted on to an excel spreadsheet. Results: 171 patients were included, of whom 148 were adults and 87 were female. The commonest indication was IDA [n = 70 (41%)]. Diarrhoea and IBD were the second most common indication with 63 patients (37%). SB abnormalities were detected in 96 patients, of which 48 had not previously been visualised on alternative investigations. This changed management in 28 patients (16%) based on the abnormalities detected. There was one complication observed; the capsule remained in the stomach stuck within rugal folds and requiring endoscopic retrieval. 44 patients with suspected CD had MRE prior to capsule endoscopy. Abnormalities were seen in 20 of these capsule endoscopies, of which 14 had not been seen in previous investigations. However, only in 5 patients (10%) did these positive capsule findings facilitate a change in their disease management. Of the 63 patients who were investigated for IBD or diarrhoea, 15 patients were diagnosed with CD in light of the VCE findings. However, of these, only 4 patients had had a change in management, of whom 3 had had findings consistent with CD already demonstrated on MRE. Conclusion: VCE is a useful and safe diagnostic test to detect SB pathology. This modality assisted management in 16% of our patient cohort. However, in the setting of IBD it appears that VCE rarely has findings that lead to a change in management over and above MRE. Reference: 1 Solem CA, Loftus EV, Jr, Fletcher JG, Baron TH, Gostout CJ, Petersen BT, et al . Small-bowel imaging in Crohn's disease: a prospective, blinded, 4-way comparison trial. Gastrointest Endosc 2008;68 (2):255–66. Disclosure of Interest: None Declared